Analysis of interest of the YouTube platform users as a medium of digital communication today - Francisca Hermawan (JURNAL MANAJEMEN, 2022)
AbstractThis research aims to analyze the interests of YouTube users related to video content and several operating techniques available on this platform. By knowing the characteristics of this interest, it is hoped that it will be gotten a picture of the future role of YouTube as a digital communication media, including in the business area. Research data obtained from 330 respondents who are the member of l public of Indonesia. They answered the questionnaire in a Google form format which was distributed via smartphones and email. Both respondents in the consumer category (audience) and the producer-consumer category were more interested in the entertainment theme. Their percentages were 58.6% and 43.6%, respectively. Meanwhile, other themes such as sports, health, education, spirituality/religion, military, socio-cultural, and business/finance were only of interest to a small number of respondents. The technical aspects of operating videos on the YouTube platform were relatively affordable for the respondents. The results of this study show that the YouTube platform is well known and in demand by the public and has the potential for wider future use, including in the business area.Key words: YouTube; Digital Media; Entertainment; Video; Internet